Modern Small Antennas. - Fujimoto, K. 1929- (Cambridge University Press, 2013)
If you need to design and develop small antennas, this complete, cutting-edge guide covers everything you need to know.
Keywords: Antennas (Electronics); Miniature electronic equipment.; elektronické knihy; electronic books